Influence of Three Phytase Preparations in Broiler Diets Based on Wheat or Corn: In vitro Measurements of Nutrient Release - Wu, Y.B.; Ravindran, V.; Pierce, J.; Hendriks, W.H. (International Journal of Poultry Science, 2004)
Using an in vitro poultry digestion model, potential beneficial effects from the side activities in a microbial phytase produced by solid state fermentation were examined by comparing the release of phosphorus, reducing sugars and alpha-amino nitrogen by two other phytase preparations in wheat- and corn-based diets. Because of the technology involved, the phytase produced by solid state fermentation is known to contain several side enzyme activities, including protease, amylase, cellulase, xylanase and beta-glucanase. Phytase produced by solid state fermentation released more (P<0.05) phytate-bound phosphorus (11.0% and 7.8% in wheat- and corn-based diets, respectively) and alpha-amino nitrogen (1.7% and 6.2% in wheat- and corn-based diets, respectively) than a phytase produced by submerged liquid fermentation, which had no detectable side activities. Phytase produced by solid state fermentation also released 2.9% more reducing sugars in the wheat-based diet and 6.2% more alpha-amino nitrogen in the corn-based diet. The superiority of this phytase product in releasing nutrients in both types of diets is likely to be due to activities of other enzymes present, but these results need to be confirmed in future in vivo studies.